2003
DOI: 10.2105/ajph.93.12.2067
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Emergency Department Analgesic Prescription

Abstract: Physicians were less likely to prescribe opioids to Blacks; this disparity appears greatest for conditions with fewer objective findings (e.g., migraine).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
221
5
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(235 citation statements)
references
References 32 publications
7
221
5
2
Order By: Relevance
“…Researchers have suggested this reflects the positive effects of assessment and treatment requirements mandated by the JCAHO [49]. Despite this, however, recent studies [68,76,91] suggest racial/ethnic inequalities in pain management in the emergency room persist. For example, in a retrospective cohort study [68] of 20,125 individuals 18 years of age or older seen for abdominal or back pain in an urban emergency department between 2003 and 2007, adjusted odds ratios for opioid administration were 1.10 (95% CI, 1.06-1.13) for white or Hispanic white patients versus African American or Hispanic African American patients, indicating a 10% greater likelihood that white individuals received opioids than African Americans.…”
Section: Acute Nonmalignant Painmentioning
confidence: 99%
“…Researchers have suggested this reflects the positive effects of assessment and treatment requirements mandated by the JCAHO [49]. Despite this, however, recent studies [68,76,91] suggest racial/ethnic inequalities in pain management in the emergency room persist. For example, in a retrospective cohort study [68] of 20,125 individuals 18 years of age or older seen for abdominal or back pain in an urban emergency department between 2003 and 2007, adjusted odds ratios for opioid administration were 1.10 (95% CI, 1.06-1.13) for white or Hispanic white patients versus African American or Hispanic African American patients, indicating a 10% greater likelihood that white individuals received opioids than African Americans.…”
Section: Acute Nonmalignant Painmentioning
confidence: 99%
“…Several studies suggest differences in function between races after joint arthroplasty [8,11,19,33]. Others have reported differences in the experience of pain by patients and in the management of that pain [8,33].…”
Section: Introductionmentioning
confidence: 99%
“…Others have reported differences in the experience of pain by patients and in the management of that pain [8,33]. Green et al [11] found chronic pain affects the quality of life and health status of the African-American population to a greater extent than in Caucasians in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Minorities may underreport pain when dealing with opposite-sex providers or with physicians perceived to be of ''higher status.'' System/provider bias is evidenced by differential pharmacy opioid stocking rates by socioeconomic region [8] or emergency room analgesia discrepancies [29]. Differences in prescribing practices for white versus nonwhite patients have also been documented in postoperative patients, patients with cancer, and patients with chronic pain in the Veterans Affairs system.…”
Section: Introductionmentioning
confidence: 99%